Effect of flywheel eccentric overload training on athletic performance: A systematic review and meta-analysis - Wang, Y.; Su, Y.; Ji, C. (Kinesiology, 2025)
This study aims to assess the effects of resistance training using flywheel devices - hereafter referred to as flywheel eccentric overload training (FEOT) - compared to conventional resistance training (including external-load resistance training and bodyweight training) on athletic performance, providing theoretical guidance and practical foundations for the scientific development of diverse training regimens. Randomized controlled trials on FEOT interventions (up to January 2024) from five Chinese/English databases were analyzed using Review Manager 5.3 and Stata-SE 15 for meta-analysis, subgroup analysis, and bias assessment. A total of 21 articles were included in this study (14 high-quality, seven moderate-quality based on the methodological assessment). The results of the meta-analysis revealed that, compared to the conventional resistance training, FEOT significantly outperformed in countermovement jump (CMJ; SMD=0.60, 95% CI: 0.2 to 0.95, p<.05), change-of-direction performance (COD; SMD=-1.23, 95% CI: -1.89 to -0.57, p<.05), and short-distance sprint performance (SMD=-0.58, 95% CI: -0.89 to -0.23, p<.05). Subgroup analysis revealed: 1) Compared to the external-load resistance training, FEOT improved CMJ (SMD=0.56, 95% CI: 0.13 to 0.99, p<.05), short-distance sprinting (SMD=-0.61, 95% CI: -0.95 to -0.27, p<.05), and COD (SMD=-1.34, 95% CI: -2.38 to -0.30, p<.05), but not 1RM strength (SMD=0.30, 95% CI: -0.50 to 1.10, p>.05). 2) Versus the bodyweight training, FEOT improved CMJ (SMD=0.77, 95% CI: 0.25 to 1.29, p<.05) and COD (SMD=-1.16, 95% CI: -2.02 to -0.30, p<.05), but not short-distance sprinting (SMD=-0.31, 95% CI: -1.47 to 0.86, p>.05). Our conclusions are: 1) compared with the conventional resistance training, FEOT yields greater improvements in CMJ, COD, and short-sprint performance and 2) FEOT outperforms external-load resistance training across CMJ, COD, and short-sprint outcomes, and shows clear advantages over bodyweight training in CMJ and COD, supporting its value as an effective strategy for enhancing explosive lower-limb performance.